Designing public communication and disclusure strategies for central banks and other policy bodies - Eva Camacho-Cuena; Simone Alfarano (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
[Introduction] The idea that a price system based on competitive markets is able to aggregate different pieces of information dispersed in the economy dates back to the 50's. In particular, economists have long understood that, in theory, the prices in properly designed asset markets reflect the collection of all the information possessed by traders on future events. Asymmetry of information among the traders is of course an essential ingredient for prices to have an informational role. Instead of leaving the market operating alone in aggregating private information, the release of public information might constitute an option that can facilitate the aggregation process. In addition to the information hold privately by traders, one might assume the existence of a disciplining institution that releases public information in order to enhance market efficiency. The public character of the information lies in the fact that it is known by all economic agents operating in the market and it is almost freely available. Intuitively, one might think that public information should be beneficial for market performance, if it is assumed that it simply cumulates to the information already present in the market: in this sense, more information seems to be beneficial for decision makers. If this might be true when an economic agent acts in isolation from others, it might not be the case when a certain strategic interaction among decision makers is introduced. The theoretical literature has shown that in an economic system where agents have access to private information, noisy public information might be weighted above and beyond its accuracy, driving the economic system far from fundamentals when wrong and therefore damaging social welfare. Using the words of Morris and Shin (2002) “public and private information (might) end up being substitute rather than being cumulative". They demonstrate that public information might be considered a double edged-instrument: it conveys information on the fundamentals of a financial asset, but, at the same time, it serves as a focal point in coordinating the traders' activity in a market. As a consequence, the noisiness of public information can be enhanced in the market due to the overreaction of the traders to the disclosure of a public signal. [...]
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: 330